Emotions and foreign language learning in online classrooms: affective strategy applications (Altre Modernità, 2022)
This article sets out to investigate the emotional aspects of foreign language learning in virtual classrooms. The pandemic has brought about a sudden transition to online and/or hybrid teaching in Italian universities, giving teachers and students new academic challenges while causing worry, stress, and anxiety. Since emotions are of fundamental importance to students’ learning as well as their wellbeing, this study explores possible interventions in the online classroom that target the emotional realities of foreign language learning and are aimed at building a safe and collaborative learning environment. Such interventions, based on affective strategies (Oxford, “Anxious Language Learners”), promote mindful learning (Langer, “Mindful Learning”) and autobiographical writing in the form of online journals in which learners can share their emotions using the foreign language.